Destination Marketing Implementationi in The Tourism Crisis Governance Policy by The Department of Tourism and Culture of West Bandung Regency - Nurzannah, Nabila Zalfa; Andari, Rini; Wulung, Shandra Rama Panji (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
The COVID-19 pandemic has had a significant impact on tourism in Indonesia, particularly in the West Bandung Regency. This study aims to comprehend the direction of destination governance policies, tourism crisis mitigation management, and the West Bandung Regency Tourism Office's implementation of tourism destination marketing in the New Habit Adaptation Era. Regulatory and marketing conditions in the West Bandung Regency area will be characterized using a descriptive approach and case study methodology. In the New Habit Adaptation Era, the results of this study indicate the direction of destination governance policies, mitigation management, and marketing in the destination area